PENGARUH PEMBERIAN AMPAS KOPI TERHADAP PERTUMBUHAN TANAMAN PAKCOY (Brassica rapa L.) - Wirna Aceh; Ujianhati Zega; Adam Smith Bago (Universitas Nias Raya, 2020)
The research was conducted in Pasar Telukdalan village, Telukdalam district, South Nias Regency starting from April 26 to May 24, 2021. This typr of research is a quantitave research with a pure experimental approach. The research design used was RAL (Competely Randomized Design) consisting of five treatments and four rreplications. The purpose of this study was to determine the effect of coffea grounds on the growth of pakcoy plants. The population of this research is pakcoy plant. The sample of this research was 20 polybags of pakcoy plants. The treatment was given with a certain dose, namely for P0 (without giving coffe grounds), P1 (100 gr), P2 (200 gr), P3 (300 gr), P4 (400 gr). The research data were analyzed by normality test, homogeneity test, hypothesis testing, and continued with further test (Duncan and LSD), with using SPSS version 20 application. Based on the results of the study, it was concluded that the administration of coffe grounds had a significant effect on plant height growth, number of leaf blades, leaf area, and productivity of pakcoy (Brassica rapa L) plants. This can be seen in the administration of coffee grounds in the fourth treatment (P4) with a dose of 400 grams. Researchers suggest in this study that people can use and utilize coffee grounds as natural fertilizer for pakcoy plants because coffee grounds contain important substances that are good for the growth of pakcoy plants (Brassica rapa L).